Profile of emotional intelligence of junior high school students - Retnoningtias, Diah Widiawati; Dewi, Ni Nyoman Ari Indra (Universitas Ahmad Dahlan, 2025)
Achieving emotional independence is one of the developmental tasks of adolescents. Previous studies have found differences in levels of emotional intelligence among adolescents. Initial studies show that the emotional intelligence of junior high school students is not optimal, especially in regulating emotions. The existence of gaps between various literature studies, gaps between literature studies and field studies, and the unavailability of research on the level of emotional intelligence, especially among students at one of the junior high schools in Denpasar, raises questions from researchers regarding the actual level of emotional intelligence of students at one of the junior high schools in Denpasar. The purpose of this study was to determine the level of emotional intelligence in students at a junior high school in Denpasar. Emotional intelligence is measured using the Emotional Intelligence Scale. The research method is descriptive quantitative. The sample was students at one of the junior high schools in Denpasar. A total of 387 respondents were determined through simple random sampling technique. The results showed that 3.87% of respondents were in the very low category, 26.87% in the low category, 40.83% in the medium category, 20.16% in the high category, and 8.27% in the very high category. The conclusion of this study is that the emotional intelligence of junior high school students has not developed optimally. The results of the study can be a reference for further researchers regarding psychological interventions to improve respondents' emotional intelligence.